2005
DOI: 10.1002/mds.20658
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Abnormal bone and calcium metabolism in immobilized Parkinson's disease patients

Abstract: To elucidate the influence of immobilization-induced hypercalcemia on bone metabolism in Parkinson's disease (PD), we measured serum biochemical indexes and bone mineral density (BMD) in the second metacarpals of 142 elderly PD patients and 99 age-matched healthy controls. Serum concentrations of 25-hydroxyvitamin D (25-OHD), 1,25-dihydroxyvitamin D (1,25-[OH](2)D), ionized calcium, intact parathyroid hormone (PTH), and intact bone Gla protein (BGP) were measured. Urinary deoxypyridinoline (D-Pyr) was also mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 38 publications
3
59
1
Order By: Relevance
“…The level of vitamin D in PD has been analysed in number of studies. A Japanese population exhibited a higher incidence of hip fractures and lower serum levels of 25OHD in PD patients as compared with the healthy controls [34,35], observations that were confirmed in a Caucasian population [9]. The serum 25OHD level correlated negatively with the severity of PD, measured in terms of the Hoehn &Yahr stage and the Unified Parkinson's Disease Rating Scale (UPDRS) [34][35][36].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The level of vitamin D in PD has been analysed in number of studies. A Japanese population exhibited a higher incidence of hip fractures and lower serum levels of 25OHD in PD patients as compared with the healthy controls [34,35], observations that were confirmed in a Caucasian population [9]. The serum 25OHD level correlated negatively with the severity of PD, measured in terms of the Hoehn &Yahr stage and the Unified Parkinson's Disease Rating Scale (UPDRS) [34][35][36].…”
Section: Introductionmentioning
confidence: 80%
“…Whereas Sato et al [34] reported a negative correlation between the 1,25OHD level and the UPDRS score, Suzuki et al [36] could not confirm this finding.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Table 1. Recommended assessment of the patient with Parkinson's disease (Mason et al 1996) population (Kao et al 1994;Sato et al 1997;Fink et al 2005;Sato et al 2005). Patients with Parkinson's disease tend to be less active than patients without the disease, and lack of sunlight absorption makes these patients more likely to be ostopenic.…”
Section: Pre -Operative Management 211 Pharmacologic Managementmentioning
confidence: 99%
“…Patients with PD are also reported to have abnormal bone metabolism (Sato et al 2005) resulting from reduced parathyroid hormone. Recent studies using teriparatide, a recombinant human parathyroid hormone, for the treatment of reduced BMD are showing promising results (Aspenberg et al 2010;Ma et al 2011;Moricke et al 2011) but so far none of the studies are related to patients with PD.…”
Section: Bone Mineral Densitymentioning
confidence: 99%